2010
DOI: 10.1007/s00415-010-5623-3
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CSF interleukin 2 receptor as indicator of neurosarcoidosis

Abstract: Neurosarcoidosis (NS) represents an important differential diagnosis of multiple sclerosis (MS). However, thus far no reliable laboratory marker of neurosarcoidosis exists. The objective of this study was to evaluate whether cerebrospinal fluid (CSF) levels of soluble interleukin 2 receptor (sIL2-R) distinguish NS and other inflammatory disorders of the central nervous system. For this purpose, 139 paired CSF and serum samples from 11 patients with NS, 21 with MS, 10 with CNS vasculitis, 22 with bacterial meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 13 publications
2
36
0
4
Order By: Relevance
“…A genetically predisposed condition of selective involvement of the nervous system can also be suggested by the evidence of a significant and specific elevation of some biomarkers in neurosarcoidosis in comparison to controls, revealing that neurosarcoidosis could be sustained partly by specific genetic profiles as found for sarcoidosis in general (29)(30)(31).…”
Section: Etiology Of Sarcoidosis and Selective Involvement Of The Nermentioning
confidence: 95%
See 1 more Smart Citation
“…A genetically predisposed condition of selective involvement of the nervous system can also be suggested by the evidence of a significant and specific elevation of some biomarkers in neurosarcoidosis in comparison to controls, revealing that neurosarcoidosis could be sustained partly by specific genetic profiles as found for sarcoidosis in general (29)(30)(31).…”
Section: Etiology Of Sarcoidosis and Selective Involvement Of The Nermentioning
confidence: 95%
“…Increased sIL2 receptor activity in the CSF might actually help to discriminate neurosarcoidosis from other chronic inflammatory CNS diseases (31). Cells in the CSF (number and type of cells) as well as antibody indices (IgM, IgA, IgG) are often pathologic and may reflect disease activity (72).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…CSF analysis shows elevated protein in about 54% cases [8]. An increased concentration of interleukin-2 receptors in CSF (over 150 pg/mL) can point towards neurosarcoidosis, although the presence of concomitant infection makes this test less sensitive [9]. Studies have shown that serum ACE level does not correlate well with disease activity due to low sensitivity and genetic polymorphism [10][11].…”
Section: Discussionmentioning
confidence: 99%
“…31 Increased CSF lactate and other markers of inflammation may also be seen. In one recent study, elevated CSF-soluble interleukin-2 receptor levels over 150 pg/mL detected untreated neurosarcoidosis patients with a 61% sensitivity and 93% specificity in comparison with healthy control subjects 33 Levels were found to change accordingly with disease activity and treatment status in serial measurements of patients with neurosarcoidosis. Although serum angiotensin-converting enzyme (ACE) is still widely used in evaluating systemic disease, CSF ACE is less helpful in the diagnosis of neurosarcoidosis given its low sensitivity (13%-25%) and has been absent even in the setting of a positive brain biopsy.…”
Section: Cerebrospinal Fluidmentioning
confidence: 92%
“…Although serum angiotensin-converting enzyme (ACE) is still widely used in evaluating systemic disease, CSF ACE is less helpful in the diagnosis of neurosarcoidosis given its low sensitivity (13%-25%) and has been absent even in the setting of a positive brain biopsy. 33,34 Cytology, flow cytometry, and cultures (fungal, bacterial, and viral) should be obtained in all patients with suspected neurosarcoidosis because malignancy and infectious meningitis may demonstrate very similar MRI and CSF findings, including hypoglycorrhachia. In known sarcoidosis patients who are chronically immunosuppressed, progressive multifocal leukoencephalopathy should be excluded with polymerase chain reaction studies for JC virus DNA.…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%